OBJEKTIVITAS TAYANGAN MATA NAJWA TRANS 7 PASCA PEMILU PRESIDEN DAN WAKIL PRESIDEN 2019 - Diah Budiantari, I Dewa Ayu; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
Objectivity is necessary to maintain credibility. Some media reports about the presidential election in Indonesia have less than 50% objectivity. The media studied in this study was Trans 7, especially the Mata Najwa show, which was the winner of the 2020 KPI Award in the news-talk show category. This study used quantitative content analysis descriptive approach by analyzing the show entitled Usai Pemilu. This study used the theory of the objectivity theory proposed by McQuail in analyzing, includes two indicators (truth and impartiality). The results of the objectivity study of Mata Najwa Trans 7 Post-election meet the items of accuracy, completeness, relevance, and non-evaluative (KPU, Bawaslu, Kubu 01, and the Survey Institute). However for factual, proportional access, two sides, non-evaluative (Kubu 02), and non-sensational items, these impressions are not presented properly. Keywords: Content Analysis, Impressions of the 2019 Presidential Election, Mata Najwa, Objectivity